Antecedents of trust using extended technology acceptance model for government social media services - Khan, Sohrab (2019)
In recent years, development of e-government services has expanded from static websites to social media. Unlike static e-government websites which are based on one-way interaction, social media is an interactive communication platform that helps to improve government public relationship through interactive participation, engagement and collaboration. However, the potential values of social media-based e-government services cannot be displayed without addressing citizens’ trust to participate in these services. Trust has been mentioned as a significant factor in adoption of e-government services. However, there is a limited focus on how to generate citizens’ trust in e-government services from multiple dimensions. Furthermore, there is a lack of prior investigation on citizens’ trust factors in the context of using social media for e-government services. To address this problem, this study aims to identify the factors that can influence citizens’ trust leading towards their intention to participate on social media for e-government services. An integrated model was developed based on multiple dimensions of citizens’ trust which are: individual characteristics, government factors, risk factors and social media characteristics. The model reflects antecedents of citizens’ trust and its influence towards their intention to participate on social media for e-government services. In this study, the positivist research approach has been used and survey methodology has been adopted to collect responses from citizens in all four provinces of Pakistan. A total of 615 valid responses were obtained and analysed by using Structural Equation Modelling with the Partial Least Squares (PLS-SEM) approach. The findings revealed that disposition to trust, benevolence, perceived privacy, perceived security, information quality, structural assurances and perceived ease of use are the factors that were found to significantly influence trust. Whereas, uncertainty avoidance, ability and integrity were found to be insignificant factors. The identified factors in this study explain 59.5 % of the variance in trust to use social media for e-government services, showing a good explanatory power of the model. Thus, this study provides valuable findings towards the development of a model that has the potential to improve citizens’ trust and their willingness to use social media for e-government services in Pakistan.